Natural edges & hollow forms [ a lesson with Chris Stott - Stott, Chris (Lesson with Chris Stott, 1994)
"The tape is intended to guide and help the more adventurous turner who wants to develop his work into the field of natural edges and to test his skills by making hollow forms"